Examining the link between Islamic work ethic and innovation capability - Samy, Naresh Kumar; Che Rose, Raduan (Emerald Group Publishing, 2010)

(untitled)
Purpose: The purpose of this paper is to present an in-depth analysis of the Islamic work ethic (IWE) and its influence on innovation capability in the public sector. Design/methodology/approach: The foundations of IWE and innovation capability were assessed using a validated questionnaire. A total of 472 employees from the Malaysian public sector participated in the survey. Findings: The empirical results indicate that the IWE is highly adapted in the public sector. In addition, the respondents collectively declared that the innovation strength in the Malaysian public sector is mounting. The IWE measure was found to be significant with moderate correlation and positive relationship with the innovation capability scale. Research limitations/implications: While the study was confined to the Malaysian public sector, it has considerable implications for the development of an optimistic workforce in other regions and across sectors. Practical implications: An understanding of the commitment of the workforce to the IWE and its consequences for innovativeness facilitates HR professionals in designing and implementing change initiatives. Originality/value: In response to the substantial need to examine IWE and workplace outcomes in a non-Western environment, therefore, the paper embraces the extent to which IWE sways innovation capability in the public sector. Both scholars and practitioners will find the study valuable.